Latest features of the ecosystem management decision support system, version 8.0 - Reynolds, K. M.; Paplanus, S.; Murphy, P. J.; Druzdzel, M. J.; Spenser, C.; Miller, B. J. (Frontiers in Environmental Science, 2023)
The Ecosystem Management Decision Support (EMDS) system is a spatially enabled system for environmental analysis and strategic and tactical planning. EMDS combines various sophisticated analytical tools within a GIS environment. Originally released by the Pacific Northwest Research Station, USDA in 1997, EMDS has been maintained and actively extended since then. Building on its core functionality of logic processing and decision modeling and availability as an ArcMap component, recent advances include more advanced geodatabase processing, integration with open-source GIS platforms, incorporation of two new analytical engines, support for scripting tools, implementation of a graphical workflow environment, advanced tactical planning, portfolio management, and a cloud-based collaboration manager. Because EMDS is a generic solution framework, it can be applied to an extremely broad array of problems at virtually any and all spatial scales. This paper presents an overview of the EMDS technology and describes some of the projects in which it has been used.